Dietary β-Mannanase Affects the Growth, Antioxidant, and Immunes Responses of African Catfish, Clarias gariepinus, and Its Challenge Against Aeromonas hydrophila Infection - Ibrahim Adeshina; Bilal Ahamad Paray; Eijaz Ahmed Bhat; Shahid Sherzada; Olaolu O. Fawole; Dalhatu J. Bawa; Thais Pereira da Cruz; Lateef O. Tiamiyu (Aquaculture Nutrition)
One of the most farmed fishes is the African catfish, Clarias gariepinus. Its production has increased by 20% annually on average during the last 20 years, but the occurrence of fish diseases, especially bacterial such as Aeromonas hydrophila infections, is hindering its activities. Also, the incorporation of plant-derived substances in aquafeeds is limited since they frequently contain different antinutritional factors, like nonstarch polysaccharides (NSPs). However, supplementing fish diets with β-mannanase could increase growth, antioxidants, and immunity. Despite the advantage of β-mannanase, its effects on growth, digestive enzymes, antioxidants, and immunity in African catfish need to be elucidated. This study examined the effects of dietary β-mannanase on the growth performance, liver enzymes, antioxidant profiles, immunity, and protection of African catfish, C. gariepinus, against A. hydrophila infection. Five isonitrogenous diets were prepared to have 400 g/kg crude protein and supplemented with β-mannanase at 0, 1500, 3000, 4500, or 6000 thermostable endo, 1,4-β-mannanase units (TMUs)/kg diet and fed to 300 juveniles of the African catfish, C. gariepinus (mean weight 12.1 ± 0.1 g) for 12 weeks. Then, 10 fish from each tank received an intraperitoneal injection of 0.1 mL of A. hydrophila (5.0 × 105 CFU/mL) and observed for 14 days. Results showed dietary β-mannanase levels considerably improved growth performance but did not affect fish survival. Also, amylase, protease, and lipase levels were significantly promoted in the fish fed with β-mannanase-fortified diets than the control group (p <0.05). Enhanced gut villi and intestinal absorption areas, haematlogical profiles, and liver enzymes but reduced gut viscosity were observed in fish-fed β-mannanase-fortified diets (p <0.05). In a dose-dependent order, including β-mannanase in the meals of African catfish raised the levels of glutathione (GSH), glutathione peroxidase (GPx), superoxide dismutase (SOD), glutathione-S-transferase (GST), and glutamate cysteine ligase (GCL) activities and decreased the malondialdehyde (MDA) values in African catfish (p <0.05). Also, fish immunity was greatly (p <0.05) enhanced due to supplementation of the diet with β-mannanase. In addition, fish-fed diets comprising 6000 TMU β-mannanase/kg diet showed the lowest rates of fish mortality (7.5%) (p <0.05). Therefore, feeding African catfish, Clarias gariepinus, β-mannanase enhanced growth performance, increased activity of digestive enzymes, gut morphology, enhanced generation of short-chain fatty acids, digesta potential of hydrogen (pH), and improved antioxidant profiles and immunity at the optimum dose of 5800 TMU/kg diet. Additionally, β-mannanase protected African catfish against A. hydrophila infection.